Analisis Aktual Efisiensi Turbin Gas Type MS5001PA - Herman Iswanto; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Minas Gas Turbine (MGT) is one of the main assets owned by the Department of Power Generation and Transmission (PG&T) operated by Chevron Indonesia Company (CPI). PG&T hasthe duty to guarantee the distribution of electricity to all assets and offices operated by Chevron Indonesia Company (CPI). Minas Gas Turbine has a Power Output of 200 - 400 MW. MGT has 11turbines that are driven by gas fuel which are processed through the Gas Power Cycle. Gas which isused as fuel is distributed by PT. Conoco Philips in Grisik located in Jambi and gas from a well owned by CPI. PLTG is a generator that has a fast response to changes in load. Therefore, changes inthe burden on PLTG often occur. To maintain the performance of the PLTG, the existing equipment in the PLTG must be maintained so that it can work optimally. In this Final Project an actual analysis ofthe efficiency of the gas turbine will be carried out on the operation load of the Gas Turbine unit # 6 type MS5001PA, by analyzing the efficiency produced by a natural gas-fired gas turbine. From theresults of this study it was found that the thermal efficiency of the Turbine Gas Turbine unit # 6 typeMS5001PA in the Minas Gas Turbine area at a load of 20 MW is 19.06%Keyword: Gas Turbine, Thermal efficiency, compressor, turbine